Real-time transabdominal ultrasound-guided ERCP is feasible and effective in pregnancy: a case series - Li, Suqing; Dargavel, Callum; Muradali, Derek; May, Gary R.; Mosko, Jeffrey D. (Endoscopy International Open, 2020)
Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) is commonly required in pregnancy for choledocholithiasis, however, radiation exposure is a major concern for patients. Real-time transabdominal (TA) ultrasound (US)-guided ERCP is a radiation-free technique that facilitates confirmation of biliary cannulation, equipment exchange and stone clearance. We present the largest Western case series of this modality in pregnancy and a review of the literature.Four pregnant adult patients were referred to our tertiary center with suspected or documented choledocholithiasis and underwent real-time TA US-guided ERCP. US was successfully used to confirm positioning of the guidewire and ductal clearance. Procedures were successful in all patients with resolution of clinical symptoms and no immediate procedural complications. Two patients suffered adverse events later in their pregnancy.Real-time TA US-guided ERCP is a technically feasible and effective modality that can be offered to obtain biliary access in a radiation-free fashion for specific subsets of pregnant patients with choledocholithiasis. Future studies are needed to confirm the safety of this technique.